Contemporary Results of the Reforming of Higher Education in China - S. S. Donetskaya; Tsyan’nan Tszi (Высшее образование в России, 2019)
The paper presents the analysis of the results of the Chinese higher education system reforming in the late 20th and early 21st century, shows the dynamics of the number of higher education institutions, the number of students and graduates. The structure of graduates in educational fields from 1995 to 2016 has been analyzed. The paper also presents the dynamics of funding of the China’s universities according to official statistics of China.The national educational reforms led to a rapid growth of the number of the universities and the number of students. Higher education has turned from the elite phenomenon to a mass one. Gross enrolment ratio in tertiary education had been increased in 9,5 times (from 1995 to 2016) and reached 42,7% in 2016. Now the Chinese government provides an extensive support to the students studying at foreign universities. It is worth mentioning that the percentage of students who had returned to China after studying abroad has been increased in three times from 28% in 1995 to 79% in 2016. The structure of graduates (according to educational fields) correlates with the needs of the growing Chinese economy: 34% of graduates have engineering professions. The largest rise of the number of graduates has been observed in economics and managerial specialties, as well as in pedagogy. The main contemporary result of the recent reforms is an international recognition of Chinese universities and a presence of the best of them in the top 100 of word university rankings.